Rekonstruksi Epistemologi Islam Dalam Gagasan Islamisasi Ilmu Pengetahuan Menurut Muhammad Naquib Al-Attas - Airawatta Al-Furqon; Nur Eka Dewi; Rany Firnandah; Laili Adnin Saputri; Dita Dwi Alifia (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2025)
The background of this study stems from the concern over the epistemological crisis afflicting the Islamic world as a result of the dominance of the secular Western paradigm, which separates knowledge from religious values. The purpose of this research is to analyze in depth the reconstruction of Islamic epistemology in the concept of the Islamization of knowledge according to Muhammad Naquib al-Attas, particularly his effort to restore knowledge to its true essence based on tawhid and the Islamic worldview. The research method employed is a literature study with a qualitative-philosophical approach, through an analysis of al-Attas’s major works and relevant supporting literature. The findings reveal that al-Attas views the crisis of knowledge among Muslims as rooted in epistemological errors caused by Western secularism, which dismisses revelation as a valid source of truth. Through the concept of Islamization of knowledge, al-Attas emphasizes the purification of fundamental scientific concepts, the restoration of scientific terminology in accordance with the Islamic worldview, and the cultivation of adab (proper conduct) as the primary orientation of education and knowledge. In conclusion, the reconstruction of Islamic epistemology in the Islamization of knowledge proposed by Muhammad Naquib al-Attas is a philosophical endeavor to return knowledge to its essence founded upon tawhid and the Islamic worldview. Al-Attas asserts that the crisis of knowledge within the Muslim world originates from epistemological confusion caused by the dominance of the secular Western paradigm that excludes revelation as a source of truth. Through Islamization of knowledge, he stresses the purification of key scientific concepts, the redefinition of scientific terms according to the Islamic worldview, and the inculcation of adab as the ultimate aim of learning. By integrating revelation, reason, and empirical experience within a harmonious hierarchy of knowledge, al-Attas successfully constructs an integrative, rational, and transcendental model of Islamic epistemology. His thought offers a new direction for the development of contemporary Islamic scholarship and education, aiming to produce civilized individuals who utilize knowledge to achieve truth, justice, and the welfare of humanity